Psychometric properties of the Arabic generalized anxiety disorder scale (GAD-5) in a non-clinical sample of Arabic-speaking adults - Toni Sawma; Pio Abd El Nour; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Sami El-Khatib; Sami El-Khatib; Feten Fekih-Romdhane; Feten Fekih-Romdhane; Souheil Hallit; Souheil Hallit; Souheil Hallit; et al. (Frontiers in Psychology)
Backgroundgeneralized anxiety disorder (GAD) is a highly prevalent psychological disorder with a frequent distribution among the general population and in primary care configurations. GAD-5 is one of the many present scales with little research on, but has the potential to orient clinical decisions due to its unique features. Validating a simple and cost-effective tool to assess the GAD in the Arabic-speaking population, primarily residing in the Middle-East and North-Africa (MENA) region, would be highly beneficial. The study aimed to translate GAD-5 into Arabic and evaluate its psychometric properties, including internal reliability, sex invariance, composite reliability, and correlation with a measure of psychological distress.Methodsa total of 629 Arabic-speaking adults were recruited in May 2023. A self-administered anonymous survey was distributed through social media using a Google Forms link. We used the SPSS AMOS software v.28 to conduct the confirmatory factor analysis of the GAD-5 scale.Resultsthe fit indices deriving from the confirmatory factor analysis indicated that the one-factor model of the GAD items was acceptable. The convergent validity for this model and the internal consistency of the scale were good. Configural, metric, and scalar invariance was supported across sex. A higher mean anxiety score was seen in females compared to males. Higher GAD-5 scores were significantly associated with higher anxiety, depression and stress as measured by the Depression, Anxiety and Stress 8 items (DASS-8) scale, showing convergent and concurrent validity.Conclusionour findings confirmed the briefness, validity and reliability of the Arabic version of the GAD-5 scale which support its employment as a screening tool in the general population. Considering these results, we advise using it for therapeutic and research motives among the Arabic-speaking individuals.